Simone Weil and the dangerous Myths of Science and Technology - Nunes da Costa , Marta (Labyrinth, 2023)
In this article I aim to clarify the role of science and technology in Weil's account of the formation and maintenance of the bureaucratic state as a totalitarian form of State, which allows to identify the similarities between capitalist, fascist and communist regimes. In the first section I characterize Weil's conception of modernity. Having The Need for Roots as my main reference, first, I reconstruct Weil's conceptualization of human nature, after I explore the meanings and signs of uprootedness and Weil's critique of Marxism. In the second section, I analyze the relationship between Revolution, Totalitarianism and the invention of the bureaucratic State. I retake Weil's critique of Marx and the Marxists arguing that science and technology must be subjected to a new criticism today, for they have been reduced to mere means of a totalitarian logic, which ultimately reinforces social oppression. I conclude by rescuing Weil's defense of the fundamental value of individual freedom and of thought, for our humanity lies in it.